Conciliação e mediação pré-processual como mecanismo de efetivação da justiça no plano da prestação jurisdicional - Luna, Jossaner Nery Nogueira (Universidade Federal do Tocantins, 2015)
The present research demonstrates the contribution mediation and pre-trail can bring to the effective access to justice in the state of Tocantins. The Access to Justice is a basic social right, guaranteed by Article 5, paragraph XXXV of the Constitution. In contemporary societies, conflicts have increased not only in number but in complexity, with many obstacles faced by the judicial system, hindering or restraining this right. Several solutions to these problems were sought, among them, alternative ways for the resolution of legal disputes, including conciliation, mediation and arbitration, which have the following advantages: low costs, speed, informality. Finally, mediation and conciliation provides new dispute resolution paradigms, in which an impartial and independent third party helps the disputants to restore the social relationship, to prevent and to solve legal disputes on their own, by organizing the dialogue between them.